Role of Glial Immunity in Lifespan Determination: A Drosophila Perspective - Kounatidis, Ilias; Chtarbanova, Stanislava (Frontiers in Immunology, 2018)
Increasing body of evidence indicates that proper glial function plays an important role in neuroprotection and in organismal physiology throughout lifespan. Work done in the model organism Drosophila melanogaster has revealed important aspects of glial cell biology in the contexts of longevity and neurodegeneration. In this mini review, we summarize recent findings from work done in the fruit fly Drosophila about the role of glia in maintaining a healthy status during animal’s life and discuss the involvement of glial innate immune pathways in lifespan and neurodegeneration. Overactive NF-κB pathways and defective phagocytosis appear to be major contributors to lifespan shortening and neuropathology. Glial NF-κB silencing on the other hand, extends lifespan possibly through an immune-neuroendocrine axis. Given the evolutionary conservation of NF-κB innate immune signaling and of macrophage ontogeny across fruit flies, rodents, and humans, the above observations in glia could potentially support efforts for therapeutic interventions targeting to ameliorate age-related pathologies.